Biodegradable adhesive tape with high printability and production process thereof
Through the combination of modified polylactic acid film and dynamic chemical bonding coating, the problems of insufficient mechanical properties and poor printing suitability of the biodegradable tape substrate are solved, and biodegradable tape with high printing suitability and multi-scene adhesion ability are achieved.
Patent Information
- Application Number
- CN202510143040.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing biodegradable tape based on polylactic acid is insufficient in the substrate, poor surface printing suitability, and insufficient adhesion and environmental durability in the substrate.
Modified polylactic acid film is used as the substrate layer, combining dynamic chemical compatibility agents and inorganic nanofillers, and designing dynamic chemical bonding coatings and double-layer adhesive layers to improve the flexibility and surface chemical activity of the substrate, enhance ink adhesion and environmental resistance.
It significantly improves the comprehensive mechanical properties of the substrate and its binding ability with the coating, improves the ink adhesion and environmental resistance, and enhances the multi-scene adhesion and biodegradation performance of the tape.
Smart Images

Figure CN119859477A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, in particular to a biodegradable adhesive tape with high printability and a production process thereof. Background Art
[0002] With the increasing global attention to environmental protection, various industries are looking for sustainable development alternatives to reduce the long-term harm of plastic waste to the ecosystem. In the packaging industry, tapes are an indispensable adhesive material and are widely used in logistics, industry and consumer goods. However, the base materials of traditional tapes are mostly made of petrochemical-based non-degradable plastics (such as polypropylene and polyvinyl chloride), which are difficult to degrade naturally after use. This not only aggravates the problem of plastic pollution, but also becomes a major burden on landfills. Biodegradable tapes have gradually become the focus of attention due to their environmental friendliness, and among them, tapes based on polylactic acid have been initially applied due to their renewability and biodegradability.
[0003] Although biodegradable tapes based on polylactic acid have natural advantages in environmental protection, there are still many technical bottlenecks in the existing technology, which limit its further application in the fields of high-performance packaging and brand printing. The polylactic acid material itself is relatively brittle, and its molecular chain lacks flexibility, resulting in insufficient toughness and limited tear resistance of the finished product. For this reason, technically, toughening agents or modification aids are usually used to physically or chemically modify polylactic acid. However, traditional toughening methods such as blending aliphatic polyesters, polycaprolactone and other substances, although they improve the flexibility of the material to a certain extent, lead to a decrease in material strength due to poor compatibility, and even cracking of the finished product surface and uneven mechanical properties. In addition, these modification methods are difficult to take into account both the performance of the substrate and its biodegradability, and often destroy the degradation uniformity of polylactic acid due to the introduction of difficult-to-degrade additives, reducing its value in environmentally friendly packaging applications.
[0004] On the other hand, printability is a key requirement for packaging tapes, but the current biodegradable tapes based on polylactic acid are still insufficient in surface coating design. Existing biodegradable tapes mostly rely on simple physical treatment methods (such as corona treatment) or single coating materials (such as acrylic coatings) to improve ink adhesion. However, such designs are difficult to maintain long-term stability in complex environments (such as high humidity or strong ultraviolet radiation). The bonding between the ink and the coating relies only on electrostatic adsorption or weak intermolecular forces, which can easily cause pattern blurring and peeling due to external stress or environmental changes, and cannot meet the needs of clear and lasting brand promotion and identification information. At the same time, due to the inertness of their chemical structure, traditional coating materials are difficult to form a strong bond with the polylactic acid substrate, further reducing the stability and overall adhesion of the coating.
[0005] In terms of adhesive layer design, traditional tapes mostly adopt a single-layer structure, and the adhesion performance mainly relies on natural rubber, acrylic materials or hot melt adhesives. However, this single-layer design is prone to aging in high humidity, high temperature or long-term use environments, which manifests as problems such as decreased peel strength and weakened adhesion. Existing technologies attempt to improve the performance of adhesives by adding plasticizers or cross-linking agents, but these methods often lead to material hardening, reduced flexibility, and may even have an adverse effect on overall biodegradability due to the complexity of the ingredients. In addition, the single-layer adhesive structure lacks stress dispersion capabilities during use, and it is difficult to maintain consistent adhesion, which is particularly insufficient in high-load adhesion scenarios. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a biodegradable tape with high printability and a production process thereof, which solves the problems of the prior art biodegradable tape in terms of insufficient mechanical properties of the substrate, poor surface printability, and insufficient adhesion and environmental durability.
[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a biodegradable tape with high printability, comprising the following structure: The substrate layer is composed of a modified polylactic acid film, wherein the modified polylactic acid film comprises polylactic acid, a dynamic chemical compatibilizer and an inorganic nanofiller; surface coatings, including dynamic chemical bond matrices, molecular capture agents, flexible hydrophobic segments, and cross-linking enhancers; The adhesive layer comprises an inner adhesive layer and an outer functional adhesive layer, wherein the inner adhesive layer comprises natural rubber and rosin-modified resin, and the outer functional adhesive layer comprises silicon-modified polyurethane and a bio-based plasticizer.
[0008] Preferably, in the substrate layer, the weight percentage of polylactic acid is 65%-75%, the weight percentage of toughening agent is 15%-25%, and the weight percentage of inorganic nanofiller is 5%-10%.
[0009] Preferably, in the surface coating, the weight percentage of the dynamic chemical bond matrix is 40%-50%, the weight percentage of the molecule capture agent is 10%-15%, the weight percentage of the flexible hydrophobic segment is 20%-25%, and the weight percentage of the cross-linking enhancer is 5%-10%.
[0010] Preferably, the weight percentage of natural rubber in the inner layer adhesive rubber is 35%-45%, the weight percentage of rosin-modified resin in the inner layer adhesive rubber is 15%-25%, the weight percentage of silicon-modified polyurethane in the outer layer functional rubber is 10%-20%, and the weight percentage of bio-based plasticizer in the outer layer functional rubber is 5%-10%.
[0011] Preferably, the dynamic chemical compatibilizer is a cyclic polyester ether, and the inorganic nanofiller is nano silicon dioxide, nano montmorillonite or nano titanium dioxide.
[0012] Preferably, the molecular capture agent is a polymer containing a guanidine group or an imidazole group, and the flexible hydrophobic segment is a fluorine-modified siloxane.
[0013] A process for producing a biodegradable adhesive tape with high printability comprises the following steps: S1. Preparation of substrate: melt-blending polylactic acid, dynamic chemical compatibilizer and inorganic nanofiller, extruding into film, and stretching on a biaxial stretching device; S2, surface coating: the dynamic chemical bond matrix, the molecular capture agent, the flexible hydrophobic segment and the cross-linking enhancer are made into a coating solution, which is evenly coated on the surface of the substrate and cured by ultraviolet light; S3, adhesive coating: coating the inner adhesive layer and the outer functional adhesive layer on the back of the substrate in sequence, and drying and curing them respectively; S4, forming and cutting: complete the winding and cut into finished tapes according to specifications.
[0014] Preferably, the substrate preparation in step S1 specifically includes the following steps: S1.1, melt blending: polylactic acid, dynamic chemical compatibilizer and inorganic nanofiller are mixed in a weight percentage ratio, and melt blended in a twin-screw extruder at a temperature of 180°C-200°C for a mixing time of 5-10 minutes; S1.2, extrusion and stretching: the molten mixture is extruded into a film through a T-die, and biaxially stretched in the temperature range of 90°C-110°C, with a stretching ratio of 2-4 times; S1.3, Cooling and shaping: The stretched film is cooled to room temperature via a cooling roller, the temperature of the cooling roller is 15°C-25°C, to form a modified polylactic acid film.
[0015] Preferably, the surface coating in step S2 specifically comprises the following steps: S2.1, preparation of coating solution: mixing the dynamic chemical bond matrix, molecular capture agent, flexible hydrophobic segment, and cross-linking enhancer according to weight percentage, stirring the coating solution at a speed of 800-1200 rpm for 20-30 min using a high-speed dispersing and stirring device, and the stirring temperature is 25°C-35°C; S2.2, coating and curing: The coating solution is evenly coated on the surface of the substrate through a micro-concave coating device, and the coating thickness is 3μm-6μm. After coating, the substrate is cured by a UV curing device. The curing light wavelength is 300-400nm and the light intensity is 20-40mW / cm 2 , the curing time is 1-5S.
[0016] Preferably, the adhesive coating in step S3 comprises the following steps: S3.1, glue solution preparation: natural rubber, rosin modified resin, silicon modified polyurethane, and bio-based plasticizer are mixed according to weight percentage to prepare inner layer adhesive glue and outer layer functional glue solution respectively; S3.2, inner layer coating: the inner layer adhesive is evenly coated on the back of the substrate with a thickness of 10μm-15μm by a doctor blade coating device, and dried at a temperature range of 60℃-80℃ for 3-5min; S3.3, outer layer coating: the outer layer functional adhesive is evenly coated on the surface of the inner layer adhesive adhesive with a thickness of 5μm-10μm by automatic spraying equipment, and dried at a temperature range of 70℃-90℃ for 5-8min.
[0017] The present invention provides a biodegradable adhesive tape with high printability and a production process thereof. It has the following beneficial effects: 1. The present invention adopts a technical solution of combining modified polylactic acid with a dynamic chemical compatibilizer, and improves the flexibility and surface chemical activity of the substrate through dynamic hydroxyl-ester exchange. Compared with the technical solution in the prior art that only uses physical toughening means (such as simple mixing of toughening agents), it solves the problems of brittleness, insufficient tensile strength and low surface activity of the traditional biodegradable tape substrate, and significantly improves the comprehensive mechanical properties of the substrate and its bonding ability with the coating.
[0018] 2. The present invention introduces polyvinylamide-ester and molecular capture agents through the design of dynamic chemical bonding coating, realizes the synergistic effect of dynamic covalent bonding and molecular adsorption, and gives the coating excellent ink adhesion and environmental resistance. Compared with the technology that simply relies on electrostatic or physical adsorption in the prior art, it solves the problems of easy ink shedding and insufficient clarity and durability of printed patterns, while ensuring the stability of the coating in complex environments (such as high humidity or ultraviolet radiation).
[0019] 3. The present invention combines natural rubber with high initial adhesion with silicon-modified polyurethane with excellent weather resistance through the inner and outer double-layer division of labor design of the adhesive layer, thereby enhancing the multi-scenario adhesion ability of the tape. Compared with the technical solution of the prior art in which the single-layer adhesive design cannot take into account both moisture and heat resistance and long-term adhesion, the present invention effectively solves the problems of adhesive aging, decreased peel strength and insufficient adhesion adaptability, while ensuring the environmental protection and practicality of the overall material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Please see attached Figure 1 The embodiment of the present invention provides a biodegradable tape with high printability, comprising the following structure: The substrate layer is composed of a modified polylactic acid film, wherein the modified polylactic acid film includes polylactic acid, a dynamic chemical compatibilizer and an inorganic nanofiller; surface coatings, including dynamic chemical bond matrices, molecular capture agents, flexible hydrophobic segments, and cross-linking enhancers; The adhesive layer comprises an inner adhesive layer and an outer functional adhesive layer, wherein the inner adhesive layer comprises natural rubber and rosin-modified resin, and the outer functional adhesive layer comprises silicon-modified polyurethane and a bio-based plasticizer.
[0023] In the substrate layer, the weight percentage of polylactic acid is 65%-75%, the weight percentage of toughening agent is 15%-25%, and the weight percentage of inorganic nano filler is 5%-10%.
[0024] In the surface coating, the weight percentage of the dynamic chemical bond matrix is 40%-50%, the weight percentage of the molecule capture agent is 10%-15%, the weight percentage of the flexible hydrophobic segment is 20%-25%, and the weight percentage of the cross-linking enhancer is 5%-10%.
[0025] The weight percentage of natural rubber in the inner layer adhesive rubber is 35%-45%, the weight percentage of rosin modified resin in the inner layer adhesive rubber is 15%-25%, the weight percentage of silicon modified polyurethane in the outer layer functional rubber is 10%-20%, and the weight percentage of bio-based plasticizer in the outer layer functional rubber is 5%-10%.
[0026] The dynamic chemical compatibilizer is cyclic polyester ether, and the inorganic nano filler is nano silicon dioxide, nano montmorillonite or nano titanium dioxide.
[0027] The molecular capture agent is a polymer containing a guanidine group or an imidazole group, and the flexible hydrophobic chain segment is a fluorine-modified siloxane.
[0028] A process for producing a biodegradable adhesive tape with high printability comprises the following steps: S1. Preparation of substrate: melt-blending polylactic acid, dynamic chemical compatibilizer and inorganic nanofiller, extruding into film, and stretching on a biaxial stretching device; S2, surface coating: the dynamic chemical bond matrix, the molecular capture agent, the flexible hydrophobic segment and the cross-linking enhancer are made into a coating solution, which is evenly coated on the surface of the substrate and cured by ultraviolet light; S3, adhesive coating: coating the inner adhesive layer and the outer functional adhesive layer on the back of the substrate in sequence, and drying and curing them respectively; S4, forming and cutting: complete the winding and cut into finished tapes according to specifications.
[0029] Step S1: Substrate preparation specifically includes the following steps: S1.1, melt blending: polylactic acid, dynamic chemical compatibilizer and inorganic nanofiller are mixed in a weight percentage ratio, and melt blended in a twin-screw extruder at a temperature of 180°C-200°C for a mixing time of 5-10 minutes; S1.2, extrusion and stretching: the molten mixture is extruded into a film through a T-die, and biaxially stretched in the temperature range of 90°C-110°C, with a stretching ratio of 2-4 times; S1.3, Cooling and shaping: The stretched film is cooled to room temperature via a cooling roller, the temperature of the cooling roller is 15°C-25°C, to form a modified polylactic acid film.
[0030] Step S2: Surface coating coating specifically includes the following steps: S2.1, preparation of coating solution: mixing the dynamic chemical bond matrix, molecular capture agent, flexible hydrophobic segment, and cross-linking enhancer according to weight percentage, stirring the coating solution at a speed of 800-1200 rpm for 20-30 min using a high-speed dispersing and stirring device, and the stirring temperature is 25°C-35°C; S2.2, coating and curing: The coating solution is evenly coated on the surface of the substrate through a micro-concave coating device, and the coating thickness is 3μm-6μm. After coating, the substrate is cured by a UV curing device. The curing light wavelength is 300-400nm and the light intensity is 20-40mW / cm 2 , the curing time is 1-5S.
[0031] The adhesive coating step S3 includes the following steps: S3.1, glue solution preparation: natural rubber, rosin modified resin, silicon modified polyurethane, and bio-based plasticizer are mixed according to weight percentage to prepare inner layer adhesive glue and outer layer functional glue solution respectively; S3.2, inner layer coating: the inner layer adhesive is evenly coated on the back of the substrate with a thickness of 10μm-15μm by a doctor blade coating device, and dried at a temperature range of 60℃-80℃ for 3-5min; S3.3, outer layer coating: the outer layer functional adhesive is evenly coated on the surface of the inner layer adhesive adhesive with a thickness of 5μm-10μm by automatic spraying equipment, and dried at a temperature range of 70℃-90℃ for 5-8min.
[0032] Example 1: Basic high printability biodegradable tape Material formula: Substrate layer: polylactic acid 70%, cyclic polyester ether (dynamic chemical compatibilizer) 15%, nano silicon dioxide 10%; Surface coating: polyvinylamide-ester (dynamic chemical bond matrix) 45%, guanidine-containing polymer (molecular capture agent) 12%, fluorine-modified siloxane (flexible hydrophobic segment) 20%, divinyl ketone (cross-linking enhancer) 8%; Adhesive layer: Inner layer adhesive: natural rubber 40%, rosin modified resin 20%; Outer layer functional adhesive: 15% silicon-modified polyurethane, 8% bio-based plasticizer; Process steps: Substrate preparation: Polylactic acid, cyclic polyester ether and nano silicon dioxide are added into a twin-screw extruder according to the formula ratio.
[0033] The temperature was set at 190°C, the screw speed was 300 rpm, and the mixing was performed for 6 min.
[0034] The mixture was extruded through a T-die to form a film, and biaxially stretched 2.5 times at 95°C.
[0035] The film was cooled to room temperature (20° C.) using a cooling roll to form a modified film having a thickness of 40 μm.
[0036] Surface coating: The dynamic chemical bond matrix, the capture agent, the hydrophobic segment and the cross-linking agent were mixed into ethanol according to a proportion, stirred at a speed of 1000 rpm, at a temperature of 30° C., and stirred for 25 minutes.
[0037] The coating solution is evenly coated on the film surface by a micro-concave coater, and the thickness is controlled to be 5 μm.
[0038] UV curing after coating, wavelength 350nm, light intensity 30mW / cm 2 , curing time 2S.
[0039] Adhesive coating: The inner layer adhesive coating thickness is 12 μm, the drying temperature is 70°C, and the drying time is 4 minutes.
[0040] The outer layer functional adhesive spraying thickness is 8μm, the drying temperature is 80℃, and the drying time is 6min.
[0041] Rolling and cutting, the width is controlled at 50mm.
[0042] Example 2: UV-resistant biodegradable tape Material formula: Base material layer: polylactic acid 68%, cyclic polyester ether 12%, nano-montmorillonite 8%; Surface coating: polyvinyl amide-ester 40%, imidazole-containing polymer 15%, fluorine-modified siloxane 25%, divinyl ketone 10%; Adhesive layer: Inner layer adhesive: natural rubber 38%, rosin modified resin 18%; Outer layer functional adhesive: 13% silicone-modified polyurethane, 6% bio-based plasticizer.
[0043] Process steps: Substrate preparation: Polylactic acid, cyclic polyester ether and nano-montmorillonite were mixed in a twin-screw extruder, the temperature was set at 185°C and the screw speed was 280 rpm.
[0044] The melting time was 7 minutes, followed by extrusion through a T-die.
[0045] The film was biaxially stretched 3 times at 90°C and cooled to 25°C to form a film.
[0046] Surface coating: The coating solution was stirred according to the recipe (speed 800 rpm, temperature 25° C., time 30 min).
[0047] Coating thickness 3μm, UV curing, wavelength 380nm, curing light intensity 35mW / cm 2 , time 3S.
[0048] Adhesive coating: The inner layer adhesive coating thickness is 10 μm, the drying temperature is 65°C, and the time is 3 minutes.
[0049] The outer layer of adhesive coating has a thickness of 7 μm, a drying temperature of 85°C, and a drying time of 5 minutes.
[0050] Roll up and cut to size.
[0051] Example 3: High peel strength biodegradable tape Material formula: Base material layer: polylactic acid 75%, cyclic polyester ether 10%, nano titanium dioxide 8%; Surface coating: polyvinylamide-ester 42%, guanidine-containing polymer 14%, fluorine-modified siloxane 20%, divinyl ketone 9%; Adhesive layer: Inner layer adhesive: natural rubber 45%, rosin modified resin 20%; Outer layer functional adhesive: 10% silicone-modified polyurethane, 7% bio-based plasticizer.
[0052] Process steps: Substrate preparation: The raw materials were mixed in a twin-screw extruder, the temperature was set to 190°C, the screw speed was 320 rpm, and the melting time was 8 min.
[0053] After extrusion, the film was biaxially stretched to 2 times at 95°C and cooled to 20°C.
[0054] Surface coating: The solution was stirred (speed 1000 rpm, time 20 min, temperature 30° C.), and the coating thickness was 4 μm.
[0055] Curing conditions: light wavelength 370nm, light intensity 40mW / cm 2 , time 2S.
[0056] Adhesive coating: The inner layer coating thickness is 15 μm, the drying temperature is 70°C, and the time is 4 minutes.
[0057] The outer coating thickness is 10 μm, the drying temperature is 85°C, and the time is 6 minutes.
[0058] Roll up and cut to required specifications.
[0059] Example 4: High transparency biodegradable tape Material formula: Base material layer: polylactic acid 70%, cyclic polyester ether 15%, nano silicon dioxide 10%; Surface coating: polyvinyl amide-ester 48%, guanidine-containing polymer 12%, fluorine-modified siloxane 22%, divinyl ketone 8%; Adhesive layer: Inner layer adhesive: natural rubber 40%, rosin modified resin 20%; Outer layer functional adhesive: 12% silicone-modified polyurethane, 5% bio-based plasticizer.
[0060] Process steps: Substrate preparation: Polylactic acid and its additives were mixed at 190°C for 7 minutes and the biaxial stretching ratio was 2.8 times.
[0061] After cooling, the transparency of the film reached 92%.
[0062] Surface coating: solution stirring speed 1000 rpm, coating thickness 4 μm, curing conditions are the same as above.
[0063] Adhesive coating: inner layer 10μm, outer layer 8μm, drying for 3min and 5min respectively.
[0064] Comparative Example 1: No dynamic chemical compatibilizer is used in the substrate layer (corresponding to Example 1) Preparation process: Material formula: polylactic acid 85%, inorganic nanofiller (nano-silicon dioxide) 10%.
[0065] This comparative example does not add a dynamic chemical compatibilizer, and only relies on the physical blending of polylactic acid and inorganic nanofiller, which is in line with the traditional technical solution.
[0066] Process flow: Melt blending: Add polylactic acid and nano-silicon dioxide into a twin-screw extruder according to the ratio, and melt mix at 190°C for 8 minutes.
[0067] Extrusion and stretching: The mixture is extruded through a T-die to form a film, biaxially stretched by 2 times at 90°C, and cooled to room temperature to form a film.
[0068] Key difference: No dynamic chemical compatibilizer is used to improve the flexibility and surface chemical activity of the substrate.
[0069] Comparative Example 2: No dynamic chemical bond matrix is used in the surface coating (corresponding to Example 2) Preparation process: Material formula: molecular capture agent (containing guanidine polymer) 15%, flexible hydrophobic segment (fluorine-modified siloxane) 25%, cross-linking enhancer (divinyl ketone) 10%.
[0070] This comparative example does not introduce a dynamic chemical bond matrix, and only forms the coating through a traditional combination of a molecule capture agent, a flexible hydrophobic segment, and a cross-linking enhancer.
[0071] Process flow: Preparation of coating solution: Mix the molecular capture agent, flexible hydrophobic segment and cross-linking enhancer into ethanol solvent according to the ratio, stir at a speed of 1000 rpm, stir for 20 min, and keep at a temperature of 30°C.
[0072] Coating and curing: The solution is coated on the substrate surface through a micro-concave coating device, the coating thickness is 4μm, the curing conditions are a wavelength of 370nm and a light intensity of 30mW / cm 2 , time is 2S.
[0073] Key difference: The dynamic chemical bond matrix is omitted, the coating lacks the ability to dynamically combine with the ink molecules, and only relies on physical adsorption and electrostatic effects to provide adhesion.
[0074] Comparative Example 3: No flexible hydrophobic segment is added to the coating (corresponding to Example 3) Preparation process: Material formula: dynamic chemical bond matrix (polyethylene amide-ester) 45%, molecular capture agent (guanidine-containing polymer) 12%, cross-linking enhancer (divinyl ketone) 8%.
[0075] In this comparative example, no flexible hydrophobic segment is added, and no hydrophobic-hydrophilic synergistic distribution is formed on the coating surface, which is consistent with the traditional coating design.
[0076] Process flow: Preparation of coating solution: The coating material was mixed into ethanol according to the proportion, with a stirring speed of 800 rpm, a time of 25 min, and a temperature of 25°C.
[0077] Coating and curing: The coating is evenly coated by the coating equipment, the thickness is controlled to be 5μm, and the curing conditions are light wavelength 350nm and light intensity 20mW / cm 2 , time is 3S.
[0078] Key difference: Lack of flexible hydrophobic segments, high surface energy of coating, insufficient hydrophobicity, which may lead to ink diffusion and contamination.
[0079] Comparative Example 4: Double-layer adhesive structure not used (corresponding to Example 4) Preparation process: Material formula: 45% natural rubber, 20% rosin modified resin.
[0080] This comparative example does not use a double-layer adhesive, but only uses a traditional single-layer adhesive formulation.
[0081] Process flow: Preparation of rubber solution: Mix natural rubber and rosin-modified resin according to the ratio, stirring speed 500 rpm, time 15 min, temperature 30°C.
[0082] Coating and drying: The adhesive was evenly coated on the back of the substrate by a knife coating device with a thickness of 15 μm, a drying temperature of 70 ° C, and a drying time of 5 minutes.
[0083] Key differences: No outer layer functional adhesive is designed, lacks environmental resistance and long-term adhesion performance, and single-layer adhesive cannot meet complex application requirements.
[0084] Comparative Example 5: No Inorganic Nanofiller Used (Corresponding to Example 1) Preparation process: Material formula: polylactic acid 85%, cyclic polyester ether 15%.
[0085] In this comparative example, no inorganic nanofiller is added, and there is no physical reinforcement network in the substrate layer, which is consistent with the traditional toughening design.
[0086] Process flow: Melt blending: Add polylactic acid and cyclic polyester ether into a twin-screw extruder in proportion and melt mix at 190°C for 6 minutes.
[0087] Extrusion and stretching: The mixture is extruded through a T-die to form a film, biaxially stretched 2.5 times at 95°C, and cooled to room temperature to form a film.
[0088] Key differences: Lack of nanofillers, weaker mechanical properties of the substrate, and lower strength, toughness and thermal stability of the film.
[0089] Comparative Example 6: No crosslinking enhancer was used (corresponding to Example 2) Preparation process: Material formula: dynamic chemical bond matrix (polyethylene amide-ester) 45%, molecular capture agent (guanidine-containing polymer) 12%, flexible hydrophobic segment (fluorine-modified silicone) 22%.
[0090] In this comparative example, no cross-linking enhancer is added, and the cured network of the coating only relies on the cross-linking of the matrix itself.
[0091] Process flow: Coating solution preparation: The materials were mixed with ethanol in proportion, with a stirring speed of 1000 rpm, a stirring time of 20 min, and a temperature of 30°C.
[0092] Coating and curing: The solution is coated by a micro-concave coating device with a thickness of 4 μm. The curing conditions are a light wavelength of 360 nm and a light intensity of 30 mW / cm 2 , time 2S.
[0093] Key difference: Without the participation of cross-linking reinforcing agent, the coating curing network is not dense enough, and the wear resistance and environmental stability are poor.
[0094] Experiment 1: Ink Adhesion Test Experimental description: Experimental purpose: To verify the advantages of the coating of the present invention in ink adhesion, and to demonstrate its effect of improving the molecular binding ability of ink through the mechanism of dynamic chemical bonding coating.
[0095] Experimental steps: Sample preparation: Take the tape samples of Example 1, Example 2, Example 3 and the corresponding Examples 2, 3 and 6, and cut them into small pieces of 50 mm×50 mm.
[0096] The same industrial ink was used to coat the sample coating surface, ensuring uniform coating with a thickness of approximately 2 μm.
[0097] Leave it for 24 hours to allow the ink to fully cure at 25°C and 50% humidity.
[0098] Cross-cut test: A cross grid was cut on the surface of each sample with a blade. The side length of the grid was 1 mm and the depth was cut to the coating.
[0099] Cover the crossed area with 3M industrial tape and press it tightly with your hands to ensure that the tape completely adheres to the coating surface.
[0100] Quickly peel off the tape at a 45° angle, observe and record the ink peeling area, and grade the adhesion according to ASTM D3359 standard.
[0101] Repeatability verification: Each sample was tested 3 times and the average result was recorded.
[0102] The test environment was controlled at 25°C and 50% humidity.
[0103] Experimental data table: Table 1: Test results of ink adhesion of samples in Experiment 1 Sample No. Test 1 Level Test 2 Level Test 3 Level Average grade Example 1 4B 5B 4B 4.3B Example 2 5B 5B 5B 5B Example 3 5B 5B 4B 4.7B Comparative Example 2 2B 3B 2B 2.3B Comparative Example 3 3B 3B 2B 2.7B Comparative Example 6 1B 2B 1B 1.3B Summary: The experimental results clearly show the adhesion advantage of the dynamic chemical bonding coating of the present invention. The adhesion grades of Example 2 and Example 3 both reached 5B or close to 5B, while Comparative Example 6 was only 1.3B. This significant difference shows that the dynamic chemical bonding matrix plays a vital role in the ink bonding process. Through the formation of dynamic covalent bonds, it can provide a stable and strong chemical bonding force between the coating and the ink, significantly enhancing the adhesion performance.
[0104] The coating design in the embodiment not only relies on the dynamic chemical bond matrix, but also combines the role of molecular capture agents. The capture agents containing guanidine and imidazole groups can actively adsorb ink molecules through electrostatic and hydrogen bonding, increasing the initial binding capacity. This is in sharp contrast to the coating of comparative example 3 that relies solely on physical adsorption. Especially in the high stress environment after the ink is cured, the molecular scale effect of the capture agent in the coating of the present invention shows great stability, which fundamentally changes the stripping behavior of the ink.
[0105] Compared with Comparative Examples 2 and 6, the flexible hydrophobic segments introduced in Example 2 also exerted a synergistic effect. The hydrophobic distribution effectively reduced the surface energy, optimized the wettability and dispersion uniformity of the ink on the coating surface, and avoided the diffusion and peeling of the ink in a high humidity environment. On the contrary, the ink adhesion of Comparative Example 3 without the addition of the hydrophobic segments was significantly reduced under high humidity conditions, further verifying the scientific nature and practical value of the functional design of the coating.
[0106] Experiment 2: Anti-ultraviolet aging performance test Experimental description: Experimental purpose: To verify the stability of the coating of the present invention under ultraviolet environment, and to compare the improvement effect of flexible hydrophobic segments and cross-linking enhancers on anti-ultraviolet performance.
[0107] Experimental steps: Sample preparation: The tape samples of Example 2, Example 4 and corresponding Examples 3 and 6 were selected.
[0108] The sample size is 50 mm × 50 mm. Ensure that the coating surface is smooth and intact, and record the initial state of the sample (such as color, gloss, and crack conditions).
[0109] UV aging test: The sample was placed in a UV aging test chamber, the light source was a UVA-340 lamp, the wavelength was set to 340nm, and the light intensity was 50W / m 2 .
[0110] The aging box temperature was set at 50°C and the relative humidity was set at 50%. The irradiation was continued for 500 h. Samples were taken every 100 h to record the changes on the coating surface.
[0111] Coating performance evaluation: After each sampling, the coating was inspected for cracks, discoloration or peeling to assess surface integrity.
[0112] After the aging process was completed, an ink adhesion test (same as Experiment 1) was performed to determine the adhesion retention of the coating after UV aging.
[0113] Repeatability verification: Test 3 groups of each sample and record the average result.
[0114] Experimental data table: Table 2: Test results of UV aging resistance of samples in Experiment 2 Summary: In Examples 2 and 4, the combination of flexible hydrophobic segments and cross-linking enhancers allows the coating surface to remain intact after long-term UV irradiation. Even after 500h aging test, the coating in Example 2 showed no cracks, only slight discoloration, and the adhesion was still maintained at the highest level of 5B. This stability is due to the cross-linking effect of the dynamic chemical bond matrix, which effectively resists UV-induced segment breakage by forming a dense three-dimensional network structure, which is unmatched by the coatings in Comparative Examples 3 and 6.
[0115] Flexible hydrophobic segments play a key role in preventing UV-induced degradation. The performance of Example 4 further verifies this point. The hydrophobic segments reduce the surface energy of the coating, making the coating absorb less water or pollutants, and avoiding the damage of the coating structure by the hot and humid environment. This is particularly evident from the test results of Comparative Example 3. The coating without flexible segments has already developed fine cracks after 100 hours of UV irradiation, and its ink adhesion has dropped sharply, indicating that the degradation process of the coating has been accelerated.
[0116] In Comparative Example 6, the coating completely lacks the support of the cross-linking enhancer, resulting in rapid aging and peeling under high-intensity ultraviolet light. This is not only a physical problem of the coating material, but also a fundamental lack of dynamic chemical design. This traditional coating scheme in the comparative example shows that the design of single chemical bond bonding cannot resist UV-induced segment breakage for a long time, while the multiple chemical bond network design of Example 2 provides higher molecular stability, thereby achieving long-term anti-ultraviolet performance.
[0117] Experiment 3: Peel strength test Experimental description: Experimental purpose: To verify the superiority of the double-layer adhesive structure of the present invention in peel strength, especially the effect of the division of labor between the inner and outer layers on improving the adhesion performance.
[0118] Experimental steps: Sample preparation: Take the tape samples of Example 1, Example 3 and corresponding Example 4 and cut them into specimens of 25 mm×150 mm.
[0119] Clean the surface of the steel plate to ensure that there is no oil or dust. Each set of samples is adhered to the steel plate and uniform pressure (2N) is applied for 10 seconds.
[0120] Peel test: A 180° peel test was performed using a tensile testing machine in accordance with GB / T2792-1998 standard.
[0121] The peeling speed was set to 300 mm / min, and the maximum peeling force (unit: N / 25 mm) required to separate the tape from the steel plate during the peeling process was recorded.
[0122] Repeatability verification: Each sample was tested 3 times and the average value was taken.
[0123] The test environment was maintained at a temperature of 23°C and a humidity of 50%.
[0124] Surface observation: record the adhesive residue after peeling and determine the peeling mode (adhesive failure, interface failure or mixed failure).
[0125] Experimental data table: Table 3: Peel strength test results of samples in Experiment 3 Summary: The peel strength test results show that the double-layer adhesive design of the present invention achieves significant performance improvement. The peel strength of Example 3 reaches 18.3N / 25mm, which is much higher than the 10.4N / 25mm of Comparative Example 4. This improvement comes from the functional division of labor and cooperation between the inner and outer adhesive layers. The inner layer adhesive is based on natural rubber and rosin-modified resin, which provides high initial adhesion and multi-surface adaptability, ensuring the strong adhesion performance of the tape. The silicon-modified polyurethane of the outer layer functional adhesive optimizes the flexibility and weather resistance of the adhesion interface, so that the adhesion remains stable during the peeling process, preventing interface peeling caused by stress concentration.
[0126] The performance of the single-layer adhesive in Comparative Example 4 verifies the necessity of this collaborative design. The single adhesive system is more likely to experience interfacial damage during the peeling process, resulting in low and unstable peeling force. In the double-layer design of the present invention, the participation of the outer layer of functional adhesive not only provides a more uniform force transmission mechanism, but also enhances the flexibility of the adhesive through the bio-based plasticizer, making the peeling process more gentle.
[0127] In addition, the observation of the peeling mode further proves the innovation of the present invention. The embodiment mainly shows a mixed failure mode of the adhesive, indicating that both the inner and outer adhesive layers play a role, and the adhesion is evenly distributed and lasting. On the contrary, in Comparative Example 4, it is more of an interface failure, and the adhesive layer cannot withstand the peeling stress, which directly leads to a significant decrease in the peeling strength. This result reveals the technical advantages of the double-layer adhesive structure in complex adhesion scenarios.
[0128] Experiment 4: Biodegradation performance test Experimental description: Experimental purpose: To verify the biodegradability of the tape of the present invention, to evaluate the degradation performance of the modified polylactic acid substrate in a soil environment with active microorganisms, and to compare its degradation rate and stability with that of the traditional toughening design.
[0129] Experimental steps: Sample preparation: The adhesive tape samples of Example 1, Example 2 and Comparative Example 1 and Comparative Example 5 were cut into small pieces of 50 mm×50 mm, and the initial mass was recorded (accurate to 0.01 g).
[0130] The samples are uniformly labeled and numbered to facilitate group comparison during testing.
[0131] Composting Degradation Test: Active microorganisms were used to compost the soil, the humidity was controlled at 60%, and the temperature was maintained at 58°C.
[0132] The sample was buried in the soil to a depth of 10 cm, ensuring complete coverage, and the timing was started.
[0133] Samples were taken out every 10 days, the attached soil was gently washed with clean water, and the samples were weighed after air drying, and the remaining mass was recorded.
[0134] Degradation rate calculation: The formula used is: degradation rate = [(initial mass - remaining mass) / initial mass] × 100%.
[0135] The test period is 60 days, and the appearance changes of the samples (such as cracks, deformation, and damage) are observed and recorded.
[0136] Repeatability verification: 3 groups of tests were performed for each sample, and the average results were taken.
[0137] Experimental data table: Table 4: Test results of biodegradability of samples in Experiment 4 Sample No. 10-day degradation rate (%) 30-day degradation rate (%) 60-day degradation rate (%) Appearance changes Example 1 12.4 38.1 67.2 Surface cracks, broken edges Example 2 15.8 45.2 79.3 Surface decomposition, overall significant reduction Comparative Example 1 5.9 19.3 41.8 No obvious cracks, slightly rough surface Comparative Example 5 7.2 22.5 47.6 No cracks on the surface, slightly deformed edges Summary: The performance of the modified polylactic acid substrate shows great degradation advantages, especially in Example 2, where the 60-day degradation rate is as high as 79.3%. In contrast, the degradation rates of Comparative Examples 1 and 5 are both less than 50%, which is a significant difference. The addition of dynamic chemical compatibilizers greatly improves the molecular chain dynamics of the substrate and provides more degradation sites.
[0138] The addition of nanofillers not only enhances the mechanical properties of the material, but also has a subtle effect on the degradation behavior. It can be observed in the experiment that cracks quickly appear on the surface of the samples of Example 1 and Example 2 at the initial stage of degradation. This is the result of inorganic fillers such as nano-silicon dioxide forming a microscopic network in the substrate. The expansion of microcracks further accelerates the microbial erosion and hydrolysis reaction, while the substrate lacking such fillers in Comparative Example 5 shows a significant degradation hysteresis phenomenon.
[0139] In addition, the optimization of the molecular orientation of the substrate by the biaxial stretching process also shows an important role. Example 2 significantly increases the flexibility of the molecular chain while maintaining the strength of the substrate by combining a higher proportion of dynamic chemical compatibilizer with stretching orientation. In Comparative Examples 1 and 5, since dynamic chemical modification is not used, the substrate exhibits lower molecular chain activity, and the degradation rate lags behind significantly in the late stage of degradation, especially during the 30 to 60 days.
[0140] Experiment 5: Coating moisture and heat resistance test Experimental description: Experimental purpose: To verify the stability of the coating of the present invention in a hot and humid environment, to compare the performance changes of the dynamic chemical bonding coating and the traditional coating under high humidity and high temperature conditions, and to evaluate the role of the flexible hydrophobic segments and cross-linking enhancers.
[0141] Experimental steps: Sample preparation: The adhesive tape samples of Example 2, Example 3 and corresponding Examples 2 and Comparative Examples 3 were selected.
[0142] Each sample was cut into a 50 mm × 50 mm block, ensuring that the surface was intact, and the initial state (such as color, gloss, and smoothness) was recorded.
[0143] Damp Heat Test: The samples were placed in a heat and humidity test chamber with the temperature inside the chamber set at 50°C and the relative humidity set at 90%.
[0144] Take out samples every 12 hours to observe whether there are cracks, peeling or discoloration on the coating surface, and record the ink adhesion level.
[0145] The total test time was 72 h, and samples were taken at the end to evaluate the overall stability of the coating.
[0146] Evaluation Methodology: The ink adhesion was tested using the ASTM D3359 standard cross-cut method and the adhesion grade was recorded.
[0147] Observe cracks and peeling of the coating, take photos and record surface changes in detail.
[0148] Repeatability verification: 3 groups of tests were performed for each sample, and the average results were taken.
[0149] Experimental data table: Table 5: Experiment 5 sample wet heat durability test results Summary: Even after 72 hours of hot and humid conditions, the coating of Example 2 still had no cracks or obvious peeling, and the ink adhesion was maintained at 5B level. This excellent performance is directly related to the dense three-dimensional network of the dynamic chemical bond matrix. Through dynamic covalent bonds, the coating can effectively resist the chemical chain segment breakage induced by the external environment under high humidity and high temperature conditions, ensuring the structural integrity of the coating.
[0150] The test performance of Example 3 further verifies the key role of the flexible hydrophobic segment. Although the gloss of the coating is slightly reduced in a hot and humid environment, the overall stability is still good. The hydrophobic segment reduces the surface energy of the coating, significantly reduces the adsorption and penetration of water molecules, and avoids the occurrence of hydrolysis reactions in a high humidity environment. In contrast, in Comparative Example 2, which lacks the design of a hydrophobic segment, cracks appear in the coating after 12 hours, and it begins to peel off after 36 hours, and the ink adhesion drops sharply.
[0151] The test results of Comparative Example 3 further verified the importance of the cross-linking enhancer. The coating lacking the cross-linking enhancer completely lost its stability after 36 hours, and the peeling phenomenon was extremely serious. This single chemical bond design lacks resistance to wet and hot conditions and cannot resist stress erosion under high temperature and high humidity conditions. The multiple chemical bond cross-linking network formed by the cross-linking enhancer in Example 2 ensures the long-term stability of the coating. The results of the wet and hot environment test verified the scientificity and practicality of the coating of the present invention in chemical design from many aspects.
[0152] Experiment 6: Tensile Strength Test Experimental description Experimental purpose: To verify the mechanical properties of the modified polylactic acid substrate of the present invention, and to evaluate its effect on improving the tensile strength of the substrate by comparing the effects of adding dynamic chemical compatibilizers and nanofillers, and the difference from traditional toughening designs.
[0153] Experimental steps: Sample preparation: The substrate samples of Example 1, Example 3 and Comparative Example 1 and Comparative Example 5 were cut into standard tensile test pieces (length 150 mm, width 20 mm, thickness equal to the original film thickness).
[0154] Ensure that the surface of each specimen is smooth and free of cracks, and the edges are neat and free of defects.
[0155] Tensile test: The tensile strength of the samples was tested using an electronic tensile testing machine.
[0156] Fix the specimen in the tensile machine fixture, keeping the fixture spacing at 100 mm.
[0157] Start the tensile testing machine, set the tensile speed to 5 mm / min, and record the maximum tensile strength (MPa) of the sample when it breaks.
[0158] Test conditions: The room temperature was 25°C and the humidity was controlled at 50%.
[0159] Each group of samples was tested 3 times and the average tensile strength value was recorded.
[0160] Data processing: Take the average of all test data and record the fluctuation of each test.
[0161] Experimental data table: Table 6: Tensile strength test results of samples in Experiment 6 Summary: From the experimental results, the tensile strength of Example 1 and Example 3 is significantly higher than that of Comparative Example 1 and Comparative Example 5, which directly proves the important role of dynamic chemical compatibilizer and nanofiller in substrate modification. Example 3 is particularly outstanding, with an average tensile strength of 55.4MPa, while Comparative Example 1 is only 32.4MPa. The dynamic chemical compatibilizer enhances the activity and compatibility of the polylactic acid molecular chain through dynamic hydroxyl-ester exchange, enabling it to disperse stress during the force process and avoid brittle fracture, which is a property that is difficult to achieve with traditional toughening agents.
[0162] The addition of nanofillers plays a dual role in improving mechanical properties. In Examples 1 and 3, nano-silicon dioxide forms a uniformly distributed physical reinforcement network, which not only increases the strength of the substrate, but also improves the dimensional stability of the substrate through the filling effect. In Comparative Example 5, due to the lack of support from this microscopic network, the tensile strength of polylactic acid can only rely on the toughening effect of physical mixing, resulting in poor performance.
[0163] The biaxial stretching process further improves the tensile strength of the substrate. The higher tensile strength in Example 3 is also due to the high degree of orientation of the polylactic acid molecular chain under biaxial stretching, which significantly improves the tensile properties of the substrate. In contrast, Comparative Examples 1 and 5 failed to fully optimize the arrangement structure of the molecular chain, and the molecular chain broke faster under high stress, resulting in obvious deficiencies in tensile properties.
[0164] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A biodegradable tape with high printability, characterized in that: Includes the following structures: The substrate layer is composed of a modified polylactic acid film, wherein the modified polylactic acid film comprises polylactic acid, a dynamic chemical compatibilizer and an inorganic nanofiller; surface coatings, including dynamic chemical bond matrices, molecular capture agents, flexible hydrophobic segments, and cross-linking enhancers; The adhesive layer comprises an inner adhesive layer and an outer functional adhesive layer, wherein the inner adhesive layer comprises natural rubber and rosin-modified resin, and the outer functional adhesive layer comprises silicon-modified polyurethane and a bio-based plasticizer.
2. The biodegradable tape with high printability according to claim 1, characterized in that: In the substrate layer, the weight percentage of polylactic acid is 65%-75%, the weight percentage of toughening agent is 15%-25%, and the weight percentage of inorganic nano filler is 5%-10%.
3. The biodegradable tape with high printability according to claim 1, characterized in that: In the surface coating, the weight percentage of the dynamic chemical bond matrix is 40%-50%, the weight percentage of the molecule capture agent is 10%-15%, the weight percentage of the flexible hydrophobic segment is 20%-25%, and the weight percentage of the cross-linking enhancer is 5%-10%.
4. The biodegradable tape with high printability according to claim 1, characterized in that: The weight percentage of natural rubber in the inner layer adhesive adhesive is 35%-45%, the weight percentage of rosin-modified resin in the inner layer adhesive adhesive is 15%-25%, the weight percentage of silicon-modified polyurethane in the outer layer functional adhesive is 10%-20%, and the weight percentage of bio-based plasticizer in the outer layer functional adhesive is 5%-10%.
5. The biodegradable tape with high printability according to claim 1, characterized in that: The dynamic chemical compatibilizer is cyclic polyester ether, and the inorganic nano filler is nano silicon dioxide, nano montmorillonite or nano titanium dioxide.
6. The biodegradable adhesive tape with high printability according to claim 1, characterized in that: The molecular capture agent is a polymer containing a guanidine group or an imidazole group, and the flexible hydrophobic segment is a fluorine-modified siloxane.
7. A process for producing a biodegradable adhesive tape with high printability, characterized in that: The following steps are involved: S1. Preparation of substrate: melt-blending polylactic acid, dynamic chemical compatibilizer and inorganic nanofiller, extruding into film, and stretching on a biaxial stretching device; S2, surface coating: the dynamic chemical bond matrix, the molecular capture agent, the flexible hydrophobic segment and the cross-linking enhancer are made into a coating solution, which is evenly coated on the surface of the substrate and cured by ultraviolet light; S3, adhesive coating: coating the inner adhesive layer and the outer functional adhesive layer on the back of the substrate in sequence, and drying and curing them respectively; S4, forming and cutting: complete the winding and cut into finished tapes according to specifications.
8. The process for producing a biodegradable adhesive tape with high printability according to claim 7, characterized in that: The substrate preparation in step S1 specifically includes the following steps: S1.1, melt blending: polylactic acid, dynamic chemical compatibilizer and inorganic nanofiller are mixed in a weight percentage ratio, and melt blended in a twin-screw extruder at a temperature of 180°C-200°C for a mixing time of 5-10 minutes; S1.2, extrusion and stretching: the molten mixture is extruded into a film through a T-die, and biaxially stretched at a temperature range of 90°C-110°C, with a stretching ratio of 2-4 times; S1.3, Cooling and shaping: The stretched film is cooled to room temperature via a cooling roller, the temperature of the cooling roller is 15°C-25°C, to form a modified polylactic acid film.
9. The process for producing a biodegradable adhesive tape with high printability according to claim 7, characterized in that: The surface coating of step S2 specifically comprises the following steps: S2.1, preparation of coating solution: mixing the dynamic chemical bond matrix, molecular capture agent, flexible hydrophobic segment, and cross-linking enhancer according to weight percentage, stirring the coating solution at a speed of 800-1200 rpm for 20-30 min using a high-speed dispersing and stirring device, and the stirring temperature is 25°C-35°C; S2.2, coating and curing: The coating solution is evenly coated on the surface of the substrate through a micro-concave coating device, and the coating thickness is 3μm-6μm. After coating, the substrate is cured by a UV curing device. The curing light wavelength is 300-400nm and the light intensity is 20-40mW / cm 2 , the curing time is 1-5S.
10. The process for producing a biodegradable adhesive tape with high printability according to claim 7, characterized in that: The adhesive coating in step S3 includes the following steps: S3.1, glue solution preparation: natural rubber, rosin modified resin, silicon modified polyurethane, and bio-based plasticizer are mixed according to weight percentage to prepare inner layer adhesive glue and outer layer functional glue solution respectively; S3.2, inner layer coating: the inner layer adhesive is evenly coated on the back of the substrate with a thickness of 10μm-15μm by a doctor blade coating device, and dried at a temperature range of 60℃-80℃ for 3-5min; S3.3, outer layer coating: the outer layer functional adhesive is evenly coated on the surface of the inner layer adhesive adhesive with a thickness of 5μm-10μm by automatic spraying equipment, and dried at a temperature range of 70℃-90℃ for 5-8min.